2020
DOI: 10.1103/physrevmaterials.4.023608
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of strongly fluctuating atomic volumes, charges, and stresses in body-centered cubic refractory high-entropy alloys

Abstract: Local lattice distortions in a series of body-centered cubic alloys, including refractory high-entropy alloys, are investigated by means of atomic volumes, atomic charges, and atomic stresses defined by the Bader charge analysis based on first-principles calculations. Analyzing the extensive data sets, we find large distributions of these atomic properties for each element in each alloy, indicating a large impact of the varying local chemical environments. We show that these local-environment effects can be we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 98 publications
(136 reference statements)
1
11
0
Order By: Relevance
“…Atomic stresses in bcc refractory HEAs are also well predicted based on the local VEC around the atoms. [84] Indeed, the correlation coefficients of DE sol and the local VEC in the 1NN shell are found to be 0.845 and 0.848 for the fcc and the hcp phases, respectively, indicating strong correlations with DE sol and the local VEC. These correlation coefficients for N in CrMnFeCoNi are much larger than those for C in CrMnFeCoNi obtained previously (0.511 and 0.597 for the fcc and the hcp phases, respectively).…”
Section: Impact Of Local Environment Around Nmentioning
confidence: 93%
“…Atomic stresses in bcc refractory HEAs are also well predicted based on the local VEC around the atoms. [84] Indeed, the correlation coefficients of DE sol and the local VEC in the 1NN shell are found to be 0.845 and 0.848 for the fcc and the hcp phases, respectively, indicating strong correlations with DE sol and the local VEC. These correlation coefficients for N in CrMnFeCoNi are much larger than those for C in CrMnFeCoNi obtained previously (0.511 and 0.597 for the fcc and the hcp phases, respectively).…”
Section: Impact Of Local Environment Around Nmentioning
confidence: 93%
“…An (NbTiZr)X alloy showed satisfactory results that matched the practical results [22], and, by using the first-principles calculation, elastic constant, modulus, and lattice parameter, the total energy of NbMoTaW and NbMoTaWV refractory high-entropy alloys was calculated [74]. The atomic properties were accurately predicted using bi-linear regression models [75], and some researchers have reported that iterative MATLAB could be used to design RHEAs. Using this method, Shafiei et al generated 40,000 alloys by changing the proportion of alloying elements in the HfMoNbTaTiVZr alloy system, and they concluded that the strength of the alloy increased with the addition of zirconium and molybdenum and decreased with the addition of titanium.…”
Section: Methodsmentioning
confidence: 65%
“…The authors discussed the relation between the atomic-stress fluctuation and the yield property of the alloys. 76) On the other hand, Ishibashi and co-workers 77) have applied our local-stress scheme to bcc HEAs consisting of refractory TM elements, and observed similar correlation between the atomic stress and charge transfer, while they observed that the results by the Bader partitioning can represent the effects of local chemical environments more reasonably, than those by the Voronoi partitioning, by incorporating the effects of realistic charge distribution between different species. The atomic charge, atomic volume and atomic stress of each constituent atom, defined by the Bader partitioning, show clear mutual correlation, which can be explained by the features of the valence electron concentration (VEC) of each atom and its first and second neighbor shells.…”
Section: Local Energy and Local Stress By Green's Functionmentioning
confidence: 67%
“…The atomic charge, atomic volume and atomic stress of each constituent atom, defined by the Bader partitioning, show clear mutual correlation, which can be explained by the features of the valence electron concentration (VEC) of each atom and its first and second neighbor shells. 77) The issue of the partitioning methods is discussed again in Sec. 5.…”
Section: Local Energy and Local Stress By Green's Functionmentioning
confidence: 99%
See 1 more Smart Citation